Analyzing the Environmental Kuznets Curve Hypothesis in Terms of Economic Growth and Different Types of Globalization in Türkiye - Melike Atay Polat; Suzan Ergün (İstanbul İktisat Dergisi)
Environmental pollution has become one of the issues most widely discussed by researchers, scientists, and policy makers these days. In particular, investigating the determinants of CO2 emissions is one of the leading areas of interest for scientists . Meanwhile, globalization causes countries to interact with each other economically, politically, and socially, and this interaction inevitably affects the environment. Therefore, globalization is an important determinant of CO2 emissions. This study aims to evaluate the dynamic effects different types of globalization (economic, social, and political) have on environmental quality in Türkiye with reference to the environmental Kuznets curve hypothesis during the 1970-2018 period using the vector error correction model (VECM). The presence of a long-term relationship among CO2 emissions per capita, GDP per capita, economic globalization, social globalization, and political globalization forTürkiye has been demonstrated using the Johansen cointegration test. According to the results, the VECM Granger causality test has determined a short-term one-way causality nexus from economic globalization to CO2 emissions and from social globalization to political globalization. In terms of long-term estimators, the study has concluded GDP per capita, economic globalization, and social globalization to significantly and positively affect CO2 emissions per capita and the square of GDP per capita and political globalization to negatively affect CO2 emissions per capita at a significant level..